Capital structure of property sector in Malaysia / Zahariah Sahudin …[et al.] - Sahudin, Zahariah; Abdullah, Hasni; Md Elias, Nura Lina; Ali, Husniyati; Anuar, Annurizal (Universiti Teknologi MARA, 2020)
The inconclusiveness of findings on the capital structure has been the main debatable topic and repeatedly discussed to date. This paper is providing new empirical evidence on the relationship between capital structure and firm efficiency by investigating the sample of Syariahcompliant property firms in Malaysia from 2002 to 2011. By employing panel data, this study is examining the factors influencing the firm leverage and analysing the dynamic aspect of the capital structure of the listed Syariah-compliant property firms in Malaysia. The study employs a parametric Stochastic Frontier Analysis (SFA) method as well, to empirically construct the property industry's 'best practice' frontier and measure the firm's efficiency as the distance from that frontier. Using these performance measures, the researchers examine how efficient firms decide debt level in their capital structure. In summary, it is found that the effects of efficiency on capital structure are as stated in the efficiency-risk hypothesis. Based on the Generalised Method of Moment (Differenced GMM), the results indicate that seven determinants are found significantly influencing the capital structure decision of the firms, particularly in the property sector in Malaysia. Those determinants are tangibility, profitability, interest coverage ratio, quick ratio, Z-Score, market-to-book ratio and efficiency. Generally, the findings support both static trade-off theory and pecking order theory for Malaysian Shariah-compliant property firms.